The ethics of Otium: pastoral, privacy and the passions 1559-1647. - Brogan, B (2012)
This thesis studies the literary genre of pastoral between 1559 and 1647. The first of these dates is that of a work that changed the course of early modern pastoral, Montemayor’s Diana; and the second marks the English translation of Gomberville’s Polexandre, a pastoral romance which exemplifies the shifts in cultural values that re-shaped Montemayor’s model over the century that followed its publication. My study focusses on the significance for this genre of the ethical quality known to classical moral philosophy as otium, and translated in early modern English by words such as peace, leisure, retirement, ease and idleness. Otium has strong historical associations with the tradition of Virgilian pastoral. Its significance in early modern pastorals, however, has been largely overlooked, despite the fact that early modern interest in otium had been revitalised by the rediscovery of some of its most important classical discussions. This renewed interest in otium, I argue, was essential to the development of early modern pastoral. My argument challenges both old and new critical perspectives on pastoral, and engages with key issues in early modern culture which literary scholars have neglected. Older studies understood pastoral otium simply as idyllic retreat; newer ones accept this view, but argue against its privileged and quietist political implications, preferring to concentrate on the tradition of interpreting pastoral as political allegory. Otium’s principal connotations, however, were neither quiet nor idyllic. Though its restorative qualities were sometimes cautiously acknowledged, otium’s potential to corrupt was ever-present, and affected a range of areas including privacy, politics, moral psychology and medicine. When people wanted to imaginatively explore those effects, I argue, pastoral was the genre to which they were most likely to turn. Listening to what pastorals say about otium can play an important role in reconstructing this crucial and misunderstood aspect of early modern culture.